Gender diversity and firm performances suffering from financial distress: Evidence~from Indonesia - Ahmad Abbas; Andi Ayu Frihatni (Journal of Capital Markets Studies (JCMS), 2023)
Purpose - This paper aims to demonstrate gender diversity in the structure of corporate governance and test the effect of diversity on the firm performance suffering from financial distress. Design/methodology/approach - The paper is quantitative using a sample of 467 public firms in Indonesia. Data were analyzed into statistics descriptive and the hypothesis was tested using the test of logistic regression. Findings - The preliminary results of the paper demonstrate the number of firms employing women and men in the structure of corporate governance of 13% on the commissioner board, 7% on the director board and 5% on the audit committee. Based on the test of effect, this paper further found that firms employing women and men (gender diversity) in the structure of the board of commissioners, tend to suffer from financial distress lower than firms only employing men (non-gender diversity). Research limitations/implications - This paper is not an effort to make the proportion of voices of women equal to men, however the representation of women at least exists in the structure of corporate governance as part of workforce diversity and inclusivity. In addition, this paper is considered not to use panel data with the purpose of avoiding repetitive data because of the use of a nominal scale in the logistic regression model. Practical implications - The finding of the paper is addressed to deliver insights into the current conversation on the issue of women's day with the theme of Each for Equal and to firms in positioning women in the structure of boardrooms. Originality/value - This paper extends the limited scholarly work on the nexus between gender diversity and financial performance. The framework of social identity theory and the tenet of corporate governance are elaborated to disclose the finding that firm shareholders tend to benefit from gender diversity in the structure of the commissioner board.
Keywords: 330; Corporate governance; Distress; Diversity; Financial performance; Gender